Anti-obesity mechanisms elucidation of essential oil components from Artemisiae Argyi Folium (Aiye) by the integration of GC-MS, network pharmacology, and molecular docking - Yongxiang Liu; Jinhai Luo; Maninder Meenu; Baojun Xu (International Journal of Food Properties)
Recently, the global epidemic of obesity is increasing significantly. Obesity is treated with anti-obesity medications and surgery and complications related to these treatments prompt the search of phytochemicals that confer anti-obesity effects. Artemisiae Argyi Folium (Aiye), a Chinese herb used as both food and medicine, exhibits potent anti-obesity effects. Aiye essential oil components are responsible for lipase activity inhibition, intestinal barrier protection, and blood lipid regulation effects. The current research aims to identify the anti-obesity essential oil components of Aiye through the integration of GC-MS, network pharmacology, and molecular docking. In present study, the Aiye essential oil components were identified by GC-MS analysis. Network pharmacology and molecular docking were integrated to predict the anti-obesity mechanisms of Aiye essential oil components. In total, 49 essential oil components were identified, containing 308 anti-obesity targets. The network pharmacology analysis revealed that the essential oil components may combat obesity through the Wnt signaling pathway, PI3K-Akt signaling pathway, MAPK signaling pathway, prolactin signaling pathway, and cAMP signaling pathway, etc. For molecular docking, there were 99 out of 140 with a binding affinity of less than −5 kcal/mol, indicating a moderate binding between essential oil components and targets. The present study revealed 308 potential anti-obesity targets of 49 essential oil components of Aiye. More than 70% of the binding between components and targets had moderate interaction. More than five anti-obesity signaling pathways of 49 Aiye essential oil components were identified. Therefore, the current research indicated that the essential oil components of Aiye may confer anti-obesity benefits.